A numerical study on smoke movement in a metro tunnel with a non-axisymmetric cross-section. (March 2018) - Zhao, Shengzhong; Liu, Fang; Wang, Fei; Weng, Miaocheng; Zeng, Zhen
Abstract: In this paper, a numerical study was carried out to analyze the effect of non-axisymmetric (semi-arched) cross-section on the smoke movement in metro tunnel fires by using FDS 6. Two models including Tunnel one (a tunnel with a non-axisymmetric cross-section) and Tunnel two (a traditional tunnel with a symmetrical section) were built. The back-layering length, critical ventilation velocity and temperature distribution were compared and analyzed. Two new prediction models for the dimensionless back-layering length and the critical ventilation velocity in semi-arched metro tunnel fires were proposed, and they were compared with the available data in previous studies and the prediction models proposed by other researchers. For the temperature distribution in Tunnel one, the maximum gas temperature beneath the ceiling appears at the center line of ceiling above the fire, and it is slightly higher than that in Tunnel two under the same fire HRR and the same ventilation velocity because of the less fresh air entrainment. In addition, the likely reasons for the different smoke movement between two tunnels were subsequently explained in this paper.